Efficacy of dynamic quadripolar radiofrequency assessed by advanced ultrasound technologies - Yu.E. Dobrokhotova; V.I. Komagorov; I.Yu. Ilina; I.I. Grishin; S.A. Zalesskaya (LCC «Medicine-Inform», 2021)
Yu.E. Dobrokhotova, V.I. Komagorov, I.Yu. Il'ina, I.I. Grishin, S.A. Zalesskaya Pirogov Russian National Research Medical University, Moscow, Russian Federation Aim: to develop a postoperative rehabilitation program for women with pelvic organ prolapse (POP). Patients and Methods: sixty postmenopausal women aged 55-75 with POP were randomized into two equal groups. All women underwent surgical intervention, which included anterior and posterior colporrhaphy and colpoperineo-levator-plasty. Group 1 women underwent five courses of radiofrequency therapy with a 14-day interval 30 days after surgery. Radiofrequency exposure was addressed by dynamic quadripolar radiofrequency (DQRF). Group 2 women were followed up without any additional rehabilitation measures. Ultrasound (US) examination using compression elastography was performed in all women To assess tissue elasticity. Neovascularization of vaginal walls was evaluated by superb microvascular imaging (SMI). The vascular intensity of the selected area of the vaginal wall was measured by automatic calculation of the vascularization index. US was performed twice, e.g., before and a fter surgery and rehabilitation (in group 1) or three months after surgery (in group 2). Results: in women who underwent DQRF therapy, an increase in the elasticity of vaginal walls was reported that indirectly demonstrates the increase in type 1 collagen and improvement of tissue vascularization. After surgery and radiofrequency therapy, the vascularization index increased by 1.6 times in group 1 and 1.2 times in group 2 compared to baseline. No postoperative complications were reported. Conclusion: this rehabilitation program is recommended for women who underwent surgical intervention for POP, given the efficacy and safety of radiofrequency therapy in the postoperative period. Keywords: pelvic organ prolapse, rehabilitation period, dynamic quadripolar radiofrequency, dynamic quadripolar radiofrequency therapy, tissue elasticity, neovascularization, elastography, superb microvascular imaging. For citation: Dobrokhotova Yu.E., Komagorov V.I., Il'ina I.Yu. et al. Efficacy of dynamic quadripolar radiofrequency assessed by advanced ultrasound technologies. Russian Journal of Woman and Child Health. 2021;4(4):311-316 (in Russ.). DOI: 10.32364/2618-8430-2021-4-4-311-316.